COVID-19 Vaccine Willingness and Hesitancy Among Marshallese Pacific Islanders. (November 2021) - McElfish, Pearl A.; Willis, Don E.; Bogulski, Cari; Kelen, Meetu; Riklon, Sheldon; Alik, Eldon; Laelan, Melisa; Brown, April L.; Sinclair, Ka'imi A.; Andersen, Jennifer A.; Amick, Benjamin C.; Williams, Mark
COVID-19 has disproportionally burdened racial and ethnic minorities. Minority populations report greater COVID-19 vaccine hesitancy; however, no studies document COVID-19 vaccine willingness among Marshallese or any Pacific Islander group, who are often underrepresented in research. This study documents United States (US) Marshallese Pacific Islanders': willingness to get the COVID-19 vaccine, willingness to participate in vaccine trials, and sociodemographic factors associated with willingness. From July 27, 2020-November 22, 2020, a convenience sample of US Marshallese adults were recruited through e-mail, phone calls, and a Marshallese community Facebook page to participate in an online survey. Of those surveyed (n = 120), 32.5% were extremely likely to get the COVID-19 vaccine; 20.8% were somewhat likely; 14.2% were unlikely or very unlikely; and 26.7% stated they did not know or were not sure. Only 16.7% stated they were willing to participate in a COVID-19 vaccine trial. Vaccine willingness was positively associated with older age, higher income, and longer US residence. Health insurance status and having a primary care provider were positively associated with vaccine willingness. Findings demonstrate within-group variation in COVID-19 vaccine willingness.